2015
DOI: 10.1159/000374064
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Alginate Addition to Resveratrol on Acute Gouty Arthritis

Abstract: Objective: Resveratrol has been shown to exert anti-inflammatory and antioxidant effects, while sodium alginate is a common pharmaceutic adjuvant with antioxidative and immunomodulatory properties. We performed an animal study to investigate the effect of sodium alginate addition to resveratrol on acute gouty arthritis. Methods: Twenty-four SPF Wistar mice were randomized to four groups receiving the combination of sodium alginate and resveratrol, resveratrol alone, colchicine, and placebo, respectively. Acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Many previous reports have indicated [36][37][38] that resveratrol can inhibit the inflammationrelated p38MAPK and NF-κB pathways to inhibit the production of inflammatory cytokines, such as COX-2, IL-6, and IL-8, and thereby inhibit the inflammatory cascade response. As a new anti-inflammatory agent, resveratrol has been used extensively in the treatment of many diseases, such as osteoarthritis [39], acute pancreatitis [40], colitis [41], esophagitis [41], acute gouty arthritis [42] and airway inflammation [43]. In the present study, various doses of resveratrol were given to a rat model of postoperative abdominal adhesions, and we found that resveratrol had a significant effect on adhesion prevention.…”
Section: Discussionmentioning
confidence: 53%
“…Many previous reports have indicated [36][37][38] that resveratrol can inhibit the inflammationrelated p38MAPK and NF-κB pathways to inhibit the production of inflammatory cytokines, such as COX-2, IL-6, and IL-8, and thereby inhibit the inflammatory cascade response. As a new anti-inflammatory agent, resveratrol has been used extensively in the treatment of many diseases, such as osteoarthritis [39], acute pancreatitis [40], colitis [41], esophagitis [41], acute gouty arthritis [42] and airway inflammation [43]. In the present study, various doses of resveratrol were given to a rat model of postoperative abdominal adhesions, and we found that resveratrol had a significant effect on adhesion prevention.…”
Section: Discussionmentioning
confidence: 53%
“…Notably, a previous study revealed that the addition of sodium alginate to resveratrol, a key effective component of CAGM, significantly enhanced its anti-inflammatory and antioxidant effects. 19 Specifically, the combination of sodium alginate and resveratrol significantly reduced the synovial levels of IL-1b, C-C chemokine receptor type 5 (CCR5), and C-X-C motif chemokine 10 (CXCL10) compared with the effects of colchicine. The combination of sodium alginate and resveratrol was also superior to resveratrol alone in terms of the serum and synovial levels of IL-1b, CCR5, and CXCL10.…”
Section: Discussionmentioning
confidence: 98%
“…Resveratrol can also reduce endothelial inflammation by reducing ICAM-1 expression and mediate protection through the miR-221/222/AMPK/p38/NF- κ B pathway [31]. In a previous study, it was shown that resveratrol could effectively treat acute gout arthritis [32]. This agent can significantly reduce joint synovial tissue edema and inflammatory cell infiltration and improve synovial hyperplasia, and its efficacy may be achieved by inhibiting the local aggregation of white blood cells into the inflammatory region and secretion of IL-1 β [33].…”
Section: Discussionmentioning
confidence: 99%